The end of October : a novel - Wright, Lawrence, 1947- (Alfred A. Knopf, 2020)
"In this propulsive medical thriller--from the Pulitzer Prize winner and best-selling author--Dr. Henry Parsons, an unlikely but appealing hero, races to find the origins and cure of a mysterious new killer virus as it brings the world to its knees. At an internment camp in Indonesia, within one week, forty-seven people are pronounced dead with acute hemorrhagic fever. When the microbiologist and epidemiologist Henry Parsons travels there on behalf of the World Health Organization to investigate, what he finds will soon have staggering repercussions across the globe: an infected man is on his way to join the millions of worshippers in the annual Hajj to Mecca. Now, Henry joins forces with a Saudi doctor and prince in an attempt to quarantine the entire host of pilgrims in the holy city. Matilda Nachinsky, deputy director of U. S. Homeland Security, scrambles to mount a response to what may be an act of biowarfare already-fraying global relations begin to snap, one by one, in the face of a pandemic. Henry's wife Jill and their children face diminishing odds of survival in Atlanta and the disease slashes across the United States, dismantling institutions--scientific, religious, governmental--and decimating the population. As packed with suspense as it is with the riveting history of viral diseases, Lawrence Wright has given us a full-tilt, electrifying, one-of-a-kind thriller"--